2020
DOI: 10.1002/adfm.202005846
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Structure and Composition Managements for High‐Performance Methylammonium‐Free Perovskite Solar Cells

Abstract: The methylammonium (MA)-free perovskite solar cells (PSCs) have drawn broad attention due to their excellent thermostability. However, the efficiency of these devices is inferior to most state-of-the-art PSCs. Herein, the photovoltaic performance of the MA-free PSCs is enhanced by constructing interfacial capping layers with a pair of alkylammonium halides, n-propylammonium (PA) iodide and propane-1,3-diammonium (PDA) iodide. The structure and composition of the interfacial layers are comprehensively investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…The effect of Cs content in FAPbI 3 was investigated in our previous work, [ 21 ] where we found an optimal doping ratio of 10% to form the Cs 0.10 FA 0.90 PbI 3 perovskite (noted CsFA hereinafter). Furthermore, the beneficial effect of adding a small amount of Rb into CsFAPI was reported in the literature, [ 31,32 ] with an optimal doping ratio of 5% that we have retained in the present work to form the Rb 0.05 Cs 0.10 FA 0.85 PbI 3 perovskite (noted RbCsFA hereinafter). Then, the influence of the addition of KI on the performance of the perovskite solar cell was investigated and the optimum amount of this metal halide was found at 5% (the details of this study are reported in Part A, Supporting Information).…”
Section: Resultsmentioning
confidence: 63%
“…The effect of Cs content in FAPbI 3 was investigated in our previous work, [ 21 ] where we found an optimal doping ratio of 10% to form the Cs 0.10 FA 0.90 PbI 3 perovskite (noted CsFA hereinafter). Furthermore, the beneficial effect of adding a small amount of Rb into CsFAPI was reported in the literature, [ 31,32 ] with an optimal doping ratio of 5% that we have retained in the present work to form the Rb 0.05 Cs 0.10 FA 0.85 PbI 3 perovskite (noted RbCsFA hereinafter). Then, the influence of the addition of KI on the performance of the perovskite solar cell was investigated and the optimum amount of this metal halide was found at 5% (the details of this study are reported in Part A, Supporting Information).…”
Section: Resultsmentioning
confidence: 63%
“…[ 18,19 ] However, the full elimination of MA + must be targeted for a better stabilization. [ 20–33 ] The most popular approach for MA‐free PSCs consists in replacing MA + by Cs + and/or by Rb + cations, two alkali metals. [ 20,21,31–33 ] Several authors have developed interfacial engineering for boosting the performances of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20,21,31–33 ] Several authors have developed interfacial engineering for boosting the performances of the devices. [ 22–24,33 ] However, in the absence of MA, PSCs usually show inferior PCEs due to an insufficient quality of the PVK material. Increasing the material crystallinity and passivating defects must be targeted.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that CsPbI 3 could not cation exchange with PEAI to form 2D PVK layer, the PEAI on the CsPbI 3 layer just formed a surface termination layer (Figure 12E), which enhanced phase stability and moisture resistance (Figure 12F). Li et al [197] . investigated the surface treatment of methylammonium‐free PVK layers by PAI and propane‐1,3‐diammonium (PDA) iodide.…”
Section: Halides At the Interfaces Of Pscsmentioning
confidence: 99%